ChemInform Abstract: Synthesis and Catalytic Relevance of P(III) and P(V)‐Functionalized Calixarenes and Resorcinarenes. Issue 47 (6th November 2014) - Semeril, David; Matt, Dominique
Abstract Review: 120 refs.